U–Pb geochronology and Hf–Nd isotopic geochemistry of the Badu Complex, Southeastern China: Implications for the Precambrian crustal evolution and paleogeography of the Cathaysia Block - Yu, Jin-Hai; O’Reilly, Suzanne Y.; Zhou, Mei-Fu; Griffin, W.L.; Wang, Lijuan (Precambrian research, 2012)
► The Badu Complex formed at 2.5Ga and was metamorphosed at 1.88Ga and 0.24Ga. ► Juvenile crust of the Cathaysia Block was generated mainly at 2.5Ga and 2.8Ga. ► Zircon U–Pb–Hf isotopes, whole-rock Nd isotopes and rock assemblages were used as a barcode to identify the tectonic affinities of the complex. ► The Cathaysia Block has a close affinity to South Korea and the Lesser Himalaya of NW India. ► The Cathaysia-S. Korea block was linked with the Lesser Himalaya in the Columbia supercontinent. The oldest rocks of the Cathaysia Block, South China, comprise the Badu Complex and Paleoproterozoic granites in the Wuyishan area (southern Zhejiang and northwestern Fujian Provinces). New zircon U–Pb ages, Hf isotopes and trace elements for metamorphic rocks from the Badu Complex, and bulk Nd-isotope compositions of these rocks and granites in the Wuyishan area provide important constraints on the Precambrian crustal evolution of the Cathaysia Block. Inherited cores of zircon grains from the metamorphic rocks are of magmatic origin, predominantly formed at ca 2.5Ga, while overgrowth rims reflect two episodes of granulite–facies metamorphism related to collisional orogeny at 1.89–1.88Ga and 252–234Ma. The unimodal age distribution (∼2.5Ga) of detrital zircons and the positive ɛHf(t) of most Neoarchean zircons suggest that the detritus of these sedimentary protoliths of the Badu Complex came from a proximal volcanic arc, and that they were deposited in an arc basin synchronously with ∼2.5Ga volcanism. Zircon U–Pb ages and Hf-isotopes with whole-rock Nd isotopes suggest that the juvenile crust of the eastern Cathaysia Block was generated mainly at 2.5Ga and 2.8Ga, and minor at 3.5–3.3Ga with some evidence for the generation at 3.7–3.6Ga and ∼4.0Ga. A strong ∼1.9Ga orogeny and the 3.3–3.0Ga thermal event only involved the reworking of older crust material. Paleoproterozoic (1.89–1.86Ga) granitic magmatic activity and high-grade metamorphism in the eastern Cathaysia Block were synchronous with the assembly of the Columbia supercontinent. Using integrated geochronological, Hf–Nd isotopic and petrologic data as a “barcode”, we compare the Cathaysia Block with other Paleoproterozoic orogens worldwide, and argue that its closest affinity is with the South Korean Peninsula and the Lesser Himalaya of NW India. Consequently, the eastern Cathaysia block, and the South Korean massif (as the united Cathay-South Korea terrane) was close to the Lesser Himalaya terrane in the Paleoproterozoic configuration of the Columbia supercontinent. The spatial linkage was maintained for ca 1Ga, until the fragmentation of the Rodinia supercontinent during Neoproterozoic time.